The Use of Mosses in Biomonitoring of Air Pollution in the Terrestrial Environment: A Review - Baczewska-Dąbrowska Aneta Helena; Gworek Barbara; Dmuchowski Wojciech (Environmental Protection and Natural Resources, 2023)
Environmental biomonitoring is an excellent supplement to instrumental methods of environmental quality assessment. The use of biological methods has many advantages (relatively low cost, independence from the source of energy in the field etc.). The limitation in the use of bioindication methods is the inability to compare the results with legal environmental pollution standards. Mosses are commonly used in air pollution monitoring. Mosses exhibit most of the characteristics attributed to effective bioindicators. The advantage of mosses over other bioindicators comes from the fact that the result depends only on-air pollution due to the lack of practical contact with the soil. Mosses are used in air pollution biomonitoring in two basic methods: naturally growing or transplanted to the researched area. They are most often used to assess air pollution by metals and other elements, but also by various organic compounds. A prerequisite for successful application of these methods is strict adherence to a recognised methodology and standardisation of all activities, such as random selection of measurement points. The article presents a critical analysis of the advantages and disadvantages of biomonitoring of air pollutants, along with a final recommendation for their use, provided that appropriate methodological rigor is maintained. An important advantage of mosses in biomonitoring is their relatively practical ease of application and interpretation of results, resulting in their widespread use.